Spiritually Driven Entrepreneurship (Cultura Económica, 2018)
Mainstream business leadership practices often produce negative impacts on nature, future generations and society as a whole. Spiritual convictions may help entrepreneurial leaders to achieve their objectives in ecological, pro-social and future respecting ways. The paper presents cases of spiritually driven entrepreneurship from the USA, Europe and India and discusses the changes required for business organizations to become sustainable.
Keywords: SPIRITUALITY; ENTREPRENEURSHOP; ECOLOGICAL SUSTAINABILITY; FUTURE GENERATIONS; PRO-SOCIALNESS